Immunocytochemical localization of a chondroitin sulfate proteoglycan in nervous tissue. I. Adult brain, retina, and peripheral nerve (The Rockefeller University Press, 1984)
Monospecific antibodies were prepared to a previously characterized chondroitin sulfate proteoglycan of brain and used in conjunction with the peroxidase-antiperoxidase technique to localize the proteoglycan by immunoelectron microscopy. The proteoglycan was found to be exclusively intracellular in adult cerebellum, cerebrum, brain stem, and spinal cord. Some neurons and astrocytes (including Golgi epithelial cells and Bergmann fibers) showed strong cytoplasmic staining. Although in the central nervous system there was heavy axoplasmic staining of many myelinated and unmyelinated fibers, not all axons stained. Staining was also seen in retinal neurons and glia (ganglion cells, horizontal cells, and Muller cells), but several central nervous tissue elements were consistently unstained, including Purkinje cells, oligodendrocytes, myelin, optic nerve axons, nerve endings, and synaptic vesicles. In sympathetic ganglion and peripheral nerve there was no staining of neuronal cell bodies, axons, myelin, or Schwann cells, but in sciatic nerve the Schwann cell basal lamina was stained, as was the extracellular matrix surrounding collagen fibrils. Staining was also observed in connective tissue surrounding the trachea and in the lacunae of tracheal hyaline cartilage. These findings are consistent with immunochemical studies demonstrating that antibodies to the chondroitin sulfate proteoglycan of brain also cross-react to various degrees with certain connective tissue proteoglycans.